Associations between total physical activity levels and academic performance in adults: A systematic review and meta-analysis - Mike Trott; Nichola Kentzer; Joanna Horne; Ben Langdown; Lee Smith (Wolters Kluwer Medknow Publications, 2024)
Physical activity has been associated with positive health-related outcomes. Physical inactivity, conversely, has been associated with several negative health outcomes. One topic that has been consistently examined is the relationship between physical activity and academic performance in children; however, studies that involve university-level students have not been aggregated to date. It is therefore the aim of this systematic review to examine the relationship between physical activity and academic performance in university-level students. This systematic review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and included any study published until September 2023 that examined associations between physical activity and any measure of academic performance. SPORTDiscus, ERIC, the British Education Index, Scopus, Embase, Web of Science, and PubMed were searched. A random effects meta-analysis was also undertaken, and risk bias was assessed using the Newcastle Ottawa Scale. After screening, 36 studies were included, with six studies being included in the meta-analysis. The meta-analysis found a significant association between physical activity (high versus low) and academic performance (high versus low performers) (odds ratio = 3.04; 95% CI = 1.84-5.02; P ≤ 0.001; I2 = 49.62). These results, however, were deemed to be of low credibility. The narrative analysis yielded mixed results, with 50% of studies reporting positive associations and the remaining studies reporting no significant associations. This trend did not differ depending on the subjective or objective measurement of physical activity. Although this review found meta-analytic significant associations between physical activity and academic performance, these results should be treated with caution, as the remaining studies yielded mixed results. Future studies should aim to focus on objective measurements of physical activity where possible to further explore this potential relationship.